Glycaemic control among women with gestational diabetes mellitus in northern Terengganu: a mixed methods study - Khalim, Mohd Adli Abd (2024)
Background: Gestational diabetes mellitus (GDM) has become a common medical condition in pregnancy and is associated with short- and long-term complications for mothers and offspring. However, information regarding poor glycaemic control is still limited in Malaysia. Objectives: This study aims to determine glycaemic control, self-efficacy, self-care, and physical activity levels, as well as factors associated with poor glycaemic control among women with GDM and to explain its significant factors based on individual experiences of women with GDM. Methodology: An explanatory sequential mixed methods study was conducted among women with GDM who attended health clinics in the Besut and Setiu districts for antenatal care. Stratified sampling proportional to size method was done in quantitative research to obtain 235 samples. Logistic regression was applied to determine associations between sociodemographic and obstetric characteristics, self-efficacy, self-care activity and physical activity with poor glycaemic control. Then, purposive sampling was done in qualitative inquiry to obtain 12 samples among women who were recruited in the quantitative research and had poor glycaemic control. Thematic analysis was applied to identify recurring themes. The data from both quantitative and qualitative inquiry were then integrated to answer research questions. Results: The mean (SD) score for overall self-efficacy was 146.89 (24.02). The mean (SD) score for self-care general diet, specific diet, physical activity, and blood glucose testing was 4.50 (1.34), 4.77 (1.35), 4.46 (1.58), and 0.45 (0.44), respectively. The median (IQR) for overall physical activity was 137.56 (112.23). Dietetic counselling (AOR=2.99; 95% CI: 1.41, 6.45; p-value=0.004) and diet self-efficacy (AOR=0.75; 95% CI: 0.57, 0.98; p-value=0.033) were associated with poor glycaemic control. There were six themes emerged from the interviews, namely: fear and worry, knowledge and motivation, dietary preferences and beliefs, family factors, occupational factors, and availability and affordability. Most of the respondents acknowledged that dietetic counselling sessions offered crucial dietary knowledge and practical integration tips, while also increasing their confidence in managing GDM more effectively. Furthermore, they demonstrated diet self-efficacy by adopting healthy eating habits, driven by personal awareness or their family members. Conclusion: Our findings showed that glycaemic control among women with GDM was influenced not only by internal factors but also external factors.